Peginterferon add‐on results in more HBsAg decline compared to monotherapy in HBeAg‐positive chronic hepatitis B patients. Issue 6 (25th September 2015) - Brouwer, W. P.; Sonneveld, M. J.; Xie, Q.; Guo, S.; Zhang, N.; Zeuzem, S.; Tabak, F.; Zhang, Q.; Simon, K.; Akarca, U. S.; Streinu‐Cercel, A.; Hansen, B. E.; et al.
Summary: It is unknown whether peginterferon (PEG‐IFN) add‐on to entecavir (ETV) leads to more HBsAg decline compared to PEG‐IFN monotherapy or combination therapy, and whether ETV therapy may prevent HBsAg increase after PEG‐IFN cessation. We performed a post hoc analysis of 396 HBeAg‐positive patients treated for 72 weeks with ETV + 24 weeks PEG‐IFN add‐on from week 24 to 48 (add‐on, n = 85), 72 weeks with ETV monotherapy ( n = 90), 52 weeks with PEG‐IFN monotherapy ( n = 111) and 52 weeks PEG‐IFN + lamivudine (combination, n = 110) within 2 randomized trials. HBsAg decline was assessed at the end of PEG‐IFN (EOP) and 6 months after PEG‐IFN (EOF) discontinuation. Differences in baseline characteristics were accounted for using inversed probability of treatment weights. At EOP, a HBsAg reduction of ≥1log10 IU/mL was more frequently achieved for patients in the add‐on or combination therapy arms (both 36%), compared to PEG‐IFN mono (20%) or ETV (8%) (add‐on vs PEG‐IFN mono P = 0.050). At EOF, the HBsAg reduction ≥1log10 IU/mL was only sustained in patients treated with ETV consolidation (add‐on vs combination and PEG‐IFN mono: 40% vs 23% and 18%, P = 0.029 and P = 0.003, respectively). For add‐on, combination, PEG‐IFN mono and ETV, the mean HBsAg‐level change at EOF was −0.84, −0.81, −0.68 and −0.33 log10 IU/mL, respectively ( P > 0.05 for PEG‐IFN arms). HBeAg loss at EOF was 36%, 31%, 33% and 20%, respectively ( P > 0.05). PEG‐IFN add‐on for 24 weeks results in more on‐treatment HBsAg decline than does 52 weeks of PEG‐IFN monotherapy. ETV therapy may maintain the HBsAg reduction achieved with PEG‐IFN.